Morphological Analysis of the Flippers in the Franciscana Dolphin, Pontoporia blainvillei, Applying X-Ray Technique - del Castillo, Daniela Laura (2014)
Pectoral flippers of cetaceans function to provide stability and maneuverability during locomotion. Directional asymmetry (DA) is a common feature among odontocete cetaceans, as well as sexual dimorphism (SD). For the first time DA, allometry, physical maturity, and SD of the flipper skeleton—by X-ray technique—of Pontoporia blainvillei were analyzed. The number of carpals, metacarpals, phalanges, and morphometric characters from the humerus, radius, ulna, and digit two were studied in franciscana dolphins from Buenos Aires, Argentina. The number of visible epiphyses and their degree of fusion at the proximal and distal ends of the humerus, radius, and ulna were also analyzed. The flipper skeleton was symmetrical, showing a negative allometric trend, with similar growth patterns in both sexes with the exception of the width of the radius (P ≤ 0.01). SD was found on the number of phalanges of digit two (P ≤ 0.01), ulna and digit two lengths. Females showed a higher relative ulna length and shorter relative digit two length, and the opposite occurred in males (P ≤ 0.01). Epiphyseal fusion pattern proved to be a tool to determine dolphin's age; franciscana dolphins with a mature flipper were, at least, four years old. This study indicates that the flippers of franciscana dolphins are symmetrical; both sexes show a negative allometric trend; SD is observed in radius, ulna, and digit two; and flipper skeleton allows determine the age class of the dolphins. Anat Rec, 297:1181–1188, 2014.